Influence of Metal ions on growth and C-Phycocyanin production in Arthrospira (Spirulina) platensis - Y.S. Mohite1 and D.U. Bhusare 2, P.S. Wakte1, (Recent Research in Science and Technology, 2011)
The present investigation was performed to analyze the influence of metal ions on growth and pigmentation of A. platensis. The metal ions in sulfate forms in five different concentrations were utilized for experiments. MgSO4 at concentrations of 1g l-1 showed optimum cell mass productivity 37.5 mg L-1 day-1 with total chlorophyll and C-PC concentrations 27.0 and 22.0 mg g-1. Zinc and copper sulphate proved to be lethal with maximum depletion in growth as well as pigment synthesis of the cyanobacterium, at 1 g l-1 the cell mass productivity was reduced to 9.2 and 4.2 mg l-1 day-1 with 1.6 and1.8 mg g-1of total chlorophyll. The C-PC concentration was reduced to 6.3 and 6.0 mg g-1. Higher concentration of CuSO4 exhibited toxicity resulting in death of the isolate. NiSO4 in lowest concentration showed 19.6 % decrease in cell mass productivity with 42.6% and 30.14% decrease in total chlorophyll and C-PC content respectively whereas MnSO4 exhibited 10.97%, 36.06% and 2.29% decrease at minimum concentration.